An assessment of knowledge, attitude, and practice regarding organ donation among students and physicians - Syed Muhammad Ashraf Jahangeer; Anooja Rani; Muhammad Abdul Rehman; Meenai, Eilaf Ahmed; Mallick, Abdul Hadi Hassan; Layiba Masroor; Muhammad Kamran (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the knowledge, attitude and practice of students and physicians regarding tissue and organ donation at a teaching hospital. Method: The cross-sectional study was conducted at the Dow University of Health Sciences, Karachi, in 2019, and comprised physicians and students of ether gender. Data was collected using a 43-item self-administered questionnaire. Dichotomous questions were scored as 1 or 0, while multiple-option questions were scored as 2, 1 or 0. Data was analysed using SPSS 25. Results: Of the 859 subjects, 761(88.6%) were students with a mean age of 20.3±1.5 years and 98(11.4%) were physicians with a mean age of 30.6±9.4. Among the students, 630(82.8%) were medical students, while 131(17.2%) were dental. The largest group among the students was of those in the second year of their studies 271(35.6%). Besides, 531(69.8%) and 64(65.3%) physician were females. Compared to males, female students reported better mean scores in terms of attitude, while higher practice scores were obtained by both male students and physicians (p=0.021). Muslim subjects scored comparatively lower in knowledge, attitude and practice terms than non-Muslims (p<0.05). Conclusion: There were high knowledge and attitude scores, while scores reflecting practice were low. Effective measures should be taken to encourage medical professionals to donate organs and promote organ donation. Key Words: Organ transplantation, Organ donation, Tissue and organ procurement, Tissue harvesting, Transplantation.